A case of thrombosis of subcutaneous anterior chest veins (Mondor's disease) as an unusual complication of botulinum type A injection. Issue 6 (September 2015) - Pisani, Laura R.; Bramanti, Placido; Calabro, Rocco S.
Abstract : Mondor's disease is a rare entity, characterized by sclerosing thrombophlebitis classically involving one or more of the subcutaneous veins, including the anterior chest wall. It is usually a self-limited, benign condition, although it may be rarely associated with cancer. The intramuscular administration of botulinum toxin type A (BoNT-A), and also, more recently, type B, is a well-established treatment of many neurological, other medical and cosmetic disorders, including strabismus, blepharospasm, cervical and other focal/segmental dystonia, and also hyperhidrosis. Herein, we describe a case of thrombosis of the subcutaneous anterior chest veins, known as Mondor's disease, following botulinum toxin treatment for armpits hyperhidrosis.